Cycloaddition of limonene epoxide and CO2 over Zn/SBA-15 catalysts for limonene carbonate synthesis (2024)
The cycloaddition reaction of CO2 with epoxides such as limonene epoxide (LE) to form cyclic carbonates is considered a promising alternative for reducing CO2 emissions. In this work, CO2 fixation on LE to produce cyclic carbonates was carried out over Zn/SBA-15 with tetrabutylammonium bromide (TBAB) as co-catalyst and over NH3X-Zn/SBA-15 (X= Cl, Br, or I) catalysts. The catalysts were characterized by FT-IR, XRD, N2 adsorption–desorption isotherms, TEM, NH3-TPD, XPS, TGA and Py-FTIR. The Zn/SBA-15 support mainly presents Lewis’s acid sites of medium acidity; the surface area was 512 m2 /g and 378 m2 /g and the pore size were 9 nm and 7.2 nm, for Zn/SBA-15 and NH3Cl-Zn/SBA-15, respectively. The functionalization of Zn/SBA-15 was verified by FTIR, UV-vis, and XPS analysis. It was found that when Zn/SBA-15 was used as catalyst that reaction time had a significative effect on LE conversion and in the case of limonene carbonate selectivity, co-catalyst concentration variation had the main effect. Zn/SBA-15 catalyst can be reused up to 5 times without significant changes neither in conversion nor in limonene carbonate selectivity. The best LE conversion and limonene carbonate selectivity was 33% and 93%, respectively (1 M LE, 200 mg Zn/SBA-15, 7% TBAB; 30 bar, 18 h, 700 rpm and 20 mL diethyl carbonate). The reported catalytic system is a promising system for obtaining limonene carbonate using a heterogeneous catalyst.